A novel fabrication method to create a thick collagen bundle composed of uniaxially aligned fibrils: An essential technology for the development of artificial tendon/ligament matrices. Issue 9 (16th March 2015) - Yunoki, Shunji; Hatayama, Hirosuke; Ebisawa, Mizue; Kondo, Eiji; Yasuda, Kazunori
Abstract In this study, we developed a fabrication method for thick collagen gel bundles comprising uniaxially aligned fibrils of sufficient size for filling defects in ligament tissues. The fabrication involved rotary shearing to dense collagen sols using a rheometer and then warming them from 23°C to 37°C to trigger gelation upon rotation. Gelation due to collagen fibril formation was accelerated by increased concentrations of neutral phosphate buffer, and fibril alignment occurred within 20 s during the early stage of rapid gelation. Fabrication of gels was completed with slippage between gels and the movable upper plate, and well‐aligned fibrils along the rotation direction were observed in the marginal regions of disc‐shaped gels. Gel thickness could be increased from 1 to 3 mm with homogeneous alignment of fibrils in the entire sample. The alignment of fibrils improved mechanical properties against tensile loads that were placed parallel to the alignment axis. Elongation of cultured fibroblast along the alignment was observed on the gels. The present method will enable the bottom–up fabrication of an artificial tendon for ligament reconstruction and repair. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3054–3065, 2015.